MALAKOK SEBAGAI DASAR INTEGRASI OLEH ETNIS MINANGKABAU DI KABUPATEN DHARMASRAYA PROVINSI SUMATERA BARAT (Malakok as a Mean for Integrition by Minangkabau Ethnic in Dharmasraya Regency, West Sumatra) - Leni Syafyahya; Efri Yades; Fajri Usman (Balai Bahasa Sumatra Barat, 2016)
AbstractIn this paper, the authors explain the procession called malakok, signs used in the processionof malakok, and the meaning of the signs used in the procession of malakok in the DistrictDharmasraya. The method used in collecting the data was the receptive method and themethod consider ably. Methods of data analysis used the (conversion) method frontier. Inaddition, the data analysis stage also used the editing and coding stage. Based on data analysis,the procession should be conducted by the person who would do malakok, who went to theprospective adoptive parents with his motehr’s brother (mamak bladder). Then, the prospectiveadoptive parents will tell the news to ninik mamak in the village. Furthermore, Ninik mamak/ Datuak will select a certain day and place. Prior to implementation, early in the morning,the women cook a meal for the event in the evening. Event praying ceremoy /Baralek started,which were attended by the invited people, Datuak from other clan, and the youth in thearea. In this malakok procession, there would pasambahan speech be delivered. Tanda-marksused in the procession malakok as a condition for the implementation of this procession,among them, namely: a goat, gold, money, and successor agreement letters. The meaning ofall signs is validation and recognition of the existence of a person in the clan in an area. AbstrakDalam tulisan ini, penulis menjelaskan prosesimalakok, tanda-tanda yang digunakan dalam prosesimalakok, dan makna tanda-tanda yang digunakan dalam prosesi malakok di KabupatenDharmasraya. Metode yang digunakan dalam pengumpulan data ialah metode simak dan metodecakap. Metode analisis data yang digunakan yaitu metode padan. Di samping itu, tahap analisis datajuga dilakukan yakni editing dan koding. Berdasarkan analisis data, prosesi yang harus dilakukanoleh pihak yang akan malakok, yaitu mendatangi calon orang tua angkatdengan membawa mamakkandung (saudara laki-laki ibu). Kemudian, calon orang tua angkat akan memberitahukan kabartersebut kepada ninik mamak yang ada di kampung. Selanjutnya, ninik mamak/datuak akan memilihhari dan tempat yang ditentukan. Sebelum pelaksanaan, pagi-paginya para ibu memasak hidanganuntuk acara di malam harinya. Acara kenduri berdoa,mendoa/baralek, dimulai yang dihadiri olehmasyarakat, datuak dari suku lain, dan para pemuda di daerah tersebut. Dalam prosesimalakokini, ada pasambahan.Tanda-tanda yang digunakan dalam prosesimalakok sebagai syarat pelaksanaanprosesi ini, di antaranya, yaitu satu ekor kambing, emas, uang, dan surat perjajian. Makna darisemua tanda itu ialah pengesahan dan pengakuan tentang keberadaan seseorang dalam persukuandi suatu daerah.